Trends in Coronary Heart Disease Epidemiology in India - Rajeev Gupta; Indu Mohan; Jagat Narula (Ubiquity Press, 2016)
Cardiovascular diseases, especially coronary heart disease (CHD), are epidemic in India. The Registrar General of India reported that CHD led to 17% of total deaths and 26% of adult deaths in 2001-2003, which increased to 23% of total and 32% of adult deaths in 2010-2013. The World Health Organization (WHO) and Global Burden of Disease Study also have highlighted increasing trends in years of life lost (YLLs) and disability-adjusted life years (DALYs) from CHD in India. In India, studies have reported increasing CHD prevalence over the last 60 years, from 1% to 9%-10% in urban populations and <1% to 4%-6% in rural populations. Using more stringent criteria (clinical ± Q waves), the prevalence varies from 1%-2% in rural populations and 2%-4% in urban populations. This may be a more realistic prevalence of CHD in India. Case-control studies have reported that important risk factors for CHD in India are dyslipidemias, smoking, diabetes, hypertension, abdominal obesity, psychosocial stress, unhealthy diet, and physical inactivity. Suitable preventive strategies are required to combat this epidemic.